Preliminary investigation on the geometric accuracy of 3D printed dental implant using a monkey maxilla incisor model - Liu, Yuchun (2023)
Additive manufacturing has proven to be a viable alternative to conventional manufacturing methodologies for metallic implants due to its capability to customize and fabricate novel and complex geometries. Specific to its use in dental applications, various groups have reported successful outcomes for customized root-analog dental implants in preclinical and clinical studies. However, geometrical accuracy of the fabricated samples has never been analyzed. In this article, we studied the geometric accuracy of a 3D printed titanium dental implant design against the tooth root of the monkey maxilla incisor. Monkey maxillas were scanned using cone-beam computed tomography, then segmentation of the incisor tooth roots was performed before the fabrication of titanium dental implants using a laser powder bed fusion (PBF) process. Our results showed 68.70% ± 5.63 accuracy of the 3D printed dental implant compared to the actual tooth (n = 8), where main regions of inaccuracies were found at the tooth apex. The laser PBF fabrication process of the dental implants showed a relatively high level of accuracy of 90.59% ± 4.75 accuracy (n = 8). Our eventual goal is to develop an accurate workflow methodology to support the fabrication of patient-specific 3D-printed titanium dental implants that mimic patients’ tooth anatomy and fit precisely within the socket upon tooth extraction. This is essential for promoting primary stability and osseointegration of dental implants in the longer term